Beetroot (Beta vulgaris) as an Anti-Inflammatory Agent in Post-CholecystectomyRecovery: A Systematic Review - Dicky Rizki Abadi Saputra; Nyoman Suci Widyastuti; Parish Budiono Bernardus (Universitas Negeri Semarang, 2026)
Background : Cholecystectomy, whether performed laparoscopically or via open approach, triggers a systemic inflammatory response characterized by elevated proinflammatory cytokines. Beetroot (Beta vulgaris) contains bioactive compounds including betalains, dietary nitrates, and polyphenols with demonstrated anti-inflammatory and antioxidant properties. This article evaluates the potential of beetroot as a natural anti-inflammatory agent in post-cholecystectomy recovery. Methods : A systematic literature search was conducted following PRISMA 2020 guidelines across PubMed, Google Scholar, and SciSpace databases. Inclusion criteria encompassed RCT and quasi-experimental studies investigating beetroot or its bioactive constituents in cholecystectomy, abdominal surgery, or relevant models of systemic inflammation. Studies were assessed for effects on inflammatory markers (C-reactive protein, interleukin-6, tumor necrosis factor-alpha) and clinical outcomes. Results No direct clinical trials of beetroot supplementation in cholecystectomy patients were identified. Evidence from related contexts demonstrated that beetroot juice supplementation reduced IL-6, TNF-alpha, and NF-κB in patients with type 2 diabetes. Animal models showed betalain-enriched extracts attenuated oxidative stress and inflammation in surgical wound healing and ischemia-reperfusion injury models.. Conclusion : While mechanistic and preclinical evidence supports the anti-inflammatory potential of beetroot constituents, direct clinical evidence in cholecystectomy patients is absent. Future perioperative trials are warranted to establish efficacy, optimal dosing, timing, and safety profiles.